Detection of pancreatic cancer tumours and precursor lesions by cathepsin E activity in mouse models. Issue 9 (7th November 2011) - Cruz-Monserrate, Zobeida; Abd-Elgaliel, Wael R; Grote, Tobias; Deng, Defeng; Ji, Baoan; Arumugam, Thiruvengadam; Wang, Huamin; Tung, Ching-Hsuan; Logsdon, Craig D
Abstract : Background and Aims: Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer death in the USA. Surgical resection is the only effective treatment; however, only 20% of patients are candidates for surgery. The ability to detect early PDAC would increase the availability of surgery and improve patient survival. This study assessed the feasibility of using the enzymatic activity of cathepsin E (Cath E), a protease highly and specifically expressed in PDAC, as a novel biomarker for the detection of pancreas-bearing pancreatic intraepithelial neoplasia (PanIN) lesions and PDAC. Methods: Pancreas from normal, chronic pancreatitis and PDAC patients was assessed for Cath E expression by quantitative real-time PCR and immunohistochemistry. Human PDAC xenografts and genetically engineered mouse models (GEMM) of PDAC were injected with a Cath E activity selective fluorescent probe and imaged using an optical imaging system. Results: The specificity of Cath E expression in PDAC patients and GEMM of pancreatic cancer was confirmed by quantitative real-time PCR and immunohistochemistry. The novel probe for Cath E activity specifically detected PDAC in both human xenografts and GEMM in vivo. The Cath E sensitive probe was also able to detect pancreas with PanIN lesions in GEMM before tumour formation. Conclusions: The elevated Cath E expression in PanIN and pancreatic tumours allowed in-vivo detection of human PDAC xenografts and imaging of pancreas with PanIN and PDAC tumours in GEMM. Our results support the usefulness of Cath E activity as a potential molecular target for PDAC and early detection imaging.